Estimation of Antioxidant and Cytotoxicity Activities of Extracts Obtained from the Leaves of Folk Medicinal Plant Benkara malabarica (Lam) - Kalusalingam, Muthiah; Balakrishnan, Veluchamy (Indian Journal of Pharmaceutical Education and Research, 2022)
Objectives: Benkara malabarica (Lam). is pharmacologically unexploited medicinal plant, used in the folklore Paliyar in India. Medicinal plant systems to treat many ailments such as cold, phlegm, stomach and body pains. The present investigation carried out with objective of finding an alternative antioxidant and cytotoxicity medicines from traditionally used medicinal plant and to provide ethnopharmacological information for its traditional usage. Materials and Methods: Petroleum ether, chloroform and methanol were used as solvents for the preparation of crude drug from the B. malabarica leaves. DPPH and O phenantroline reduction assay were used to estimate the antioxidant activities of the extracts, while MTT assay was used to determine the cytotoxicity of extracts using Hep G2 cell lines. Different concentration of extracts, in the range of 25, 50, 100, 150 and 200 μg/ml was used for the determination of antioxidant activities. In case of cytotoxicity studies the extract concentration were 25, 50, 100, 200 and 500 μg/ml. Ascorbic acid was used as standard in antioxidant studies and doxorubicin was employed as standard in the cytotoxicity studies. Results: In both antioxidant and cytotoxicity studies, the activities were increased with the increase the concentrations of extracts. The potential of three extracts were in the following order, methanol, chloroform and petroleum ether in both antioxidant and cytotoxicity studies. Conclusion: The remarkable antioxidant and cytotoxicity activities, assayed through various in vitro models in the present study. This may be due to the presence of phytochemicals, such as phenol, flavonoid, alkaloid and glycosides in the extracts. Scientific data generated from the present study supports the usage of B. malabarica in the folklore medicinal system.
Keywords: Paliyar; Benkara malabarica; in vitro; Antioxidant activity; Cytotoxicity